(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2015)
Introduction. Today a multiple-unit antenna properties, containing big number DRs are studied inefficiently. At present article a possibility of the antennas building produced on paraboloidal lattices consisting DRs of the cylindrical form with lowest magnetic type resonances is considered. The results. Calculation results of the antenna parameters on dielectric resonator paraboloidal lattices are presented. The space distribution of the radiation field patterns in the near and wave zones is considered. Reflection coefficient frequency dependence of the antennas is calculated. Possibility narrowing of the directional pattern is showed. Signals frequency selection performing as well as increased electromagnetic compatibility of the suggested structures is noticed. Conclusion. Adduced calculations indicate capability of the practical application lattices on DRs as well as building on their base a wide class of the frequency selective antennas in millimeter and sub millimeter wavelength ranges. Such antennas will have enhanced electromagnetic compatibility.